Pengaruh Kepemimpinan Kepala Sekolah dan Kompetensi Guru terhadap Motivasi serta Implikasinya pada Kinerja Guru (Studi Deskriptif Kuantitatif di Sekolah Dasar Negeri Baros Kencana Cipta Mandiri) - Yeni Suminar; Kosasih Kosasih; Dety Mulyanti (Journal on Education, 2023)
Based on a preliminary study conducted by researchers regarding the principal's leadership and teacher competence at the Baros Kencana Cipta Bina Mandiri Public Elementary School, several initial field facts were found, namely 1) The principal in carrying out his leadership was able to mobilize teachers, students and school members to always improve their abilities even though there are several obstacles, this is proven based on data from the Education Report Card. 2) Some teachers have carried out and maximized their work as teachers, but there are still some students who still need special intervention by their teachers. The purpose of this study is to analyze the influence of principal leadership and teacher competence on motivation and the implications for teacher performance. The benefits of providing additional information to develop a theoretical basis strategy regarding the Influence of Principal Leadership and Teacher Competence on Motivation and the Implications for Teacher Performance. This study uses a quantitative research method with a descriptive approach. The results of the study show that the results of the ANOVA calculation obtained information about the results of the calculation Fcount = 3.788 > Ttable = 1.98 and probability (Sig.) 078a which means greater than the significance level of 0.05, so that it can be decided that Ha which reads "There is a significant influence significantly on the principal's leadership, teacher competence and motivation on teacher performance". The results of the correlation calculation presented in the table show the adjusted R2 result of 0.482. This means that the influence of the principal's leadership variable (X1), teacher competence (X2), and motivation (Y) on teacher performance (Z) is 48.2% while the remaining 50.8% is influenced by the variables in this study.